PARTISIPASI MASYARAKAT DESA SEBASANG DALAM PELAKSANAAN PEMBANGUNAN DESA TAHUN 2024 - Kesi Jusmita; Aldi Apriansyah (Nusantara Hasana Journal, 2026)
This study aims to analyze the forms of community participation in Sebasang Village in implementing village development and the factors influencing it. The study employed a qualitative descriptive method with a case study approach. Data collection was conducted through observation, interviews, and documentation of informants directly related to the research focus. The results indicate that community participation in village development has been implemented at the planning, implementation, utilization, and evaluation stages, but the level of participation is not yet optimal. Participation is still dominated by certain groups with relatively low levels of community presence and active participation. Community participation is influenced by internal factors, such as education level, employment, and community awareness, as well as external factors including information transparency, accountability, responsiveness, consensus, equality, effectiveness, and efficiency of village development implementation. Therefore, an active role is needed by the village government in realizing transparent, accountable, and participatory development governance to increase community participation and support sustainable village development.